Levels of Anxiety and Fear Related to Non-Surgical Root Canal Treatment Performed by Endodontic Residents and Endodontists - Maha Alghofaily; Fahd Alsalleeh (Frontiers Media S.A., 2022)
ObjectivesDespite advances in endodontic treatment procedures, root canal treatment is still associated with anxiety and fear. This may cause care avoidance and subsequent oral complications due to untreated endodontic infections. Anxiety and fear levels in response to non-surgical root canal treatment performed by endodontic residents and endodontists were analyzed.MethodsA descriptive, cross-sectional survey was conducted among patients visiting the endodontic clinics at the University Dental Hospital. The questions addressed the participant's demographics, previous root canal treatment visits, clinician's level of training, and post-treatment experience.ResultsDemographics play a role in anxiety and dental fear in root canal treatment. Men scored significantly lower in the high-anxiety category than women, and patients treated by endodontic residents expressed lower levels of anxiety. Post-treatment experience of an endodontist or endodontic resident was a significant factor in reducing dental fear and anxiety.ConclusionThe level of anxiety and fear related to root canal experience of endodontists or endodontic residents is very low. Most of the patients expressed willingness to undergo further root canal treatment to save a tooth.